STRATEGI PENGELOLAAN AREAL DENGAN KONSERVASI TINGGI PADA PERKEBUNAN KELAPA SAWIT (STUDI KASUS PT ADEI PLANTATION & INDUSTRY KEBUN MANDAU) - Reby Oktarianda; Nofrizal Nofrizal; Suwondo Suwondo (Jurnal Ilmu Lingkungan, 2022)
The journey of the development of oil palm plantations in Indonesia has always been tinged with negative accusations and influences on export bans at the global level (world market). Facing these allegations, Indonesia has a sustainable oil palm plantation scheme contained in Permentan No. 38 of 2020 which contains the obligation of plantation businesses to own and manage areas with high conservation (NKT) in the company's operational area (HGU). The existence of NKT area in the plantation area becomes a mandatory requirement for sustainable oil palm plantations to be accepted by the world market. This research is important to do because, until now, the study of NKT area management strategies in oil palm plantation areas is still very lacking. This research was conducted at PT Adei Plantation & Industry Kebun Mandau, using survey methods and further analyzed using SWOT. The results of the study obtained the need for PT Adei Plantation & Industry Kebun Mandau to form a special institution of NKT management to manage NKT Area within the HGU area.